Analisis Implementasi Regulasi Pendidikan Antikorupsi pada Pendidikan Dasar dan Menengah - Zulaiha, Aida Ratna; Sukirman, Dadang; Rusman (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Anti-corruption education (ACC), especially in formal education at primary and secondary levels, is a strategic step to eradicate corruption in forming a generation with integrity and anti-corruption. However, the Regional Head Regulation on PAK, as the legal basis for the integration of anti-corruption values in the curriculum in education units, its implementation shows significant variations between local governments. This study analyzes the implementation of the PAK regulation in primary and secondary education, and evaluates its success through a descriptive qualitative approach. The results show that although 83% of local governments have issued regulations, implementation at the school level still varies. The main constraints include lack of understanding, teacher training and technical guidance. Success factors include adherence to good governance principles, completeness of regulations and effective socialization. This study recommends improved coordination between local governments and education units, continuous training for teachers, provision of innovative materials, and regular monitoring and evaluation to ensure the consistency of regulation implementation and the effectiveness of anti-corruption education implementation.